[Waiting for the big bang ; Better safe than sorry ; Amnesty International [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1992)
An investigative report on the eruption of Mount Mayon; the controversy between the church and the government on how much to promote the use of the condom; and the Amnesty International working actively in the Philippines.
Waiting for a big bang (10 min.) -- Better safe than sorry (21 min.) -- Amnesty International (15 min.)
VHS.
Keywords: Amnesty International; AIDS (Disease); Civil rights -- Philippines; Disaster victims -- Philippines -- Bicol; Mayon Volcano (Albay) -- Eruption, 1992.